Ultrafast spin dynamics: complementing theoretical analyses by quantum state measures. (29th March 2023) - Ziolkowski, Franziska; Busch, Oliver; Mertig, Ingrid; Henk, Jürgen
Abstract: In theoretical analyses of ultrafast spin dynamics simulated phenomena are commonly discussed in terms of observables. In this paper we report on possible benefits of complementing such studies by quantum state (QS) measures. These measures quantify specific properties of QSs, e.g. distance in Hilbert space and mixing. For Co/Cu heterostructures illuminated by femtosecond laser pulses, we discuss the general behavior of selected measures, but address in particular the degree of perturbation by a laser pulse. It turns out that the measures are especially sensitive to variations of the polarization of a laser pulse and the sample composition. Moreover, they are closely linked to magnetization and number of photo-excited electrons.